PENYULUHAN DAN PEMANFAATAN SHORT MESSAGE SERVICE UNTUK MENINGKATKAN PENGETAHUAN DAN KEPATUHAN MINUM OBAT PADA PENDERITA TUBERKULOSIS DI KECAMATAN SUKAWATI GIANYAR - dhyana putri (Poltekkes Kemenkes Denpasar, 2020)
Abstract Background, Pulmonary Tuberculosis (TB) is an infectious disease caused by Mycobacterium tuberculosis. Pulmonary TB disease is transmitted through airborne droplet infection with the source of infection is a person with a cough pulmonary TB disease. The duration of treatment for tuberculosis patients requires a long time, which is 6-8 months treatment time, patients do not understand the importance of TB disease treatment rules, the emergence of OAT resistance, lack of government supervision of treatment programs and community culture that considers TB as a hereditary disease or curse, these problems can be a reason for a person with tuberculosis not compliant in carrying out treatment and even stop treatment. Purpose, Community service aims to increase the knowledge and compliance of taking medication for Tuberculosis patients in the Sukawati Sub-District, Gianyar Regency. The method is carried out by providing counseling with booklet media and sending SMS regularly every day for one month. Results Characteristics of tuberculosis patients in the Sukawati sub-district of Gianyar were mostly aged 21-40 years (48.1%), female (63%), primary school education level (51.9%) and work as craftsmen (37%). Knowledge about tuberculosis with tuberculosis before counseling was largely lacking (85.2%), after being given counseling most knowledge about tuberculosis was good (77.8%). Adherence to taking medication for tuberculosis patients 96.3% adhere to medication. Keywords: Tuberculosis, Counseling, SMS